Diagnostic approach to a functional adrenal tumour in a Shih-Tzu Poodle mix - Tan, L. P.; Thong, Hoe Foong; Lim, Sue Yee (Veterinary Association Malaysia, 2016)
Hyperadrenocorticism is the excessive production of cortisol by the adrenal cortex. 15-20% of hyperadrenocorticism in dogs may be due to functional adrenal tumour. Here we present a case of functional adrenal tumour in a 10 years old Shih-Tzu Poodle mixed-breed dog that was presented to University Veterinary Hospital, Universiti Putra Malaysia. Physical examination findings include multiple cutaneous myiasis, a pendulous abdomen with comedones on the ventral thoracic region and thinning of the skin. Clinical signs shown were polyuria, polydipsia and polyphagia. Serum biochemistry result showed elevated alkaline phosphatase enzyme of 5 folds. Urinary specific gravity was minimally concentrated (1.015). Radiography showed generalised hepatomegaly. Meanwhile, ultrasonography showed unilateral enlargement of the right adrenal gland with mineralisation. Invasion of the right adrenal gland into the caudal vena cava was observed. A differentiation test (high-dose dexamethasone suppression test) was performed and a lack of suppression of the cortisol level was observed. Based on the appropriate clinical signs and physical examination findings, elevated alkaline phosphatase enzyme, minimally concentrated urinary specific gravity, generalised hepatomegaly, unilateral adrenal gland enlargement, and high-dose dexamethasone suppression test, a diagnosis of functional adrenal tumour was made.